Pengaruh Customer Experience & Customer Trust Terhadap Repurchase Intention Di KKV Makassar Dengan Impulsive Buying Sebagai Mediator - Amelia, Azarine Nahdah; Munajah, Siti; Fianto, Achmad Yanu Alif (Ecobuss, 2024)
This research aims to investigate the influence of customer experience and customer trust on repurchase intention through impulsive buying as an intervening variable in KKV customers. The population used in this study consisted of KKV customers in Makassar City. Data were collected through the distribution of questionnaires in Google Form. The sampling technique used was non-probability with convenience sampling. The sample used consisted of 79 respondents. The data analyzed using SPSS statistical software version 23 then were processed and analyzed through descriptive statistical tests, validity tests, reliability tests, classical assumption tests, linear regression tests, and moderator variable tests. This study indicate that customer experience has a positive and significant effect on impulsive buying, customer trust does not have a significant effect on impulsive buying, customer experience does not have a significant effect on repurchase intention, customer trust has a positive and significant effect on repurchase intention, impulsive buying has a positive and significant effect on repurchase intention, impulsive buying has a positive and significant effect as a intervening variable of customer experience on repurchase intention, and impulsive buying does not have a significant effect as a intervening variable of customer trust on repurchase intention.